Hypolipidemic and Antioxidant Activity of Enoki Mushrooms (Flammulina velutipes). (31st August 2014) - Yeh, Ming-Yei; Ko, Wen-Ching; Lin, Li-Yun
Abstract : According to the literatures, Flammulina velutipes contains biologically active components such as dietary fiber, polysaccharide, and mycosterol, whose effects in reducing blood sugar, blood pressure, and cholesterol have been proven. This study used the active components extracted from Flammulina velutipes powder (FVP) and Flammulina velutipes extract (FVE) to investigate the impact of these active components on lipid metabolism of hamsters. The results show that the total dietary fiber content in FVP and FVE is 29.34 mg/100 g and 15.08 mg/100 g, respectively. The total mycosterol content is 46.57 ± 0.37 mg/100 g and 9.01 ± 0.17 mg/100 g, respectively. The male hamsters were subjected to lipid metabolism monitoring by adding 1, 2, and 3% FVP or FVE into their diets for a period of 8 weeks. The animal assay results show that the 3% FVP and FVE groups have the lowest concentration of TC (total cholesterol), TG (triacylglycerol), LDL (low density lipoprotein cholesterol), and LDL/HDL (high density lipoprotein cholesterol) in the serum and liver ( P < 0.05). Our results demonstrate that the addition of 3% FVP or FVE has a significant effect on the lipid metabolism in hamsters whose increased level of HDL in the serum was induced by high fat diet.